2013
DOI: 10.1073/pnas.1218682110
|View full text |Cite
|
Sign up to set email alerts
|

Rare somatic cells from human breast tissue exhibit extensive lineage plasticity

Abstract: We identified cell surface markers associated with repression of p16 INK4a

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
73
1

Year Published

2013
2013
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(81 citation statements)
references
References 34 publications
7
73
1
Order By: Relevance
“…Initial investigations indicated that cells positive for pluripotency genes are present in the mammary epithelium, both its ductal and alveolar compartments, and in substantially larger numbers during lactation than in the resting breast (18,54). This further supports a role for these cells and the pluripotency genes they express in the remodeling of the mammary gland toward a milk-secretory organ.…”
Section: Breast Milk Stem Cellsmentioning
confidence: 83%
See 1 more Smart Citation
“…Initial investigations indicated that cells positive for pluripotency genes are present in the mammary epithelium, both its ductal and alveolar compartments, and in substantially larger numbers during lactation than in the resting breast (18,54). This further supports a role for these cells and the pluripotency genes they express in the remodeling of the mammary gland toward a milk-secretory organ.…”
Section: Breast Milk Stem Cellsmentioning
confidence: 83%
“…In both cases, indirect evidence supports the notion that they play critical roles. In the mammary gland, they appear to be important during its remodeling toward a milk-secretory organ, as is suggested by the higher expression of pluripotency genes during pregnancy, when epithelial expansion occurs, and the rarity of these cells in the resting breast (18,54). In the infant, the substantial number of these stem cells ingested daily during breastfeeding (thousands to millions) implies a function (2).…”
Section: Functions Of Breast Milk Stem Cellsmentioning
confidence: 99%
“…À in adult human breasts (Roy et al 2013). The presence of pluripotent cells in the adult gland (Hassiotou et al 2012;Roy et al 2013) or the possible persistence of fetal MaSCs into adulthood has profound implications for breast oncogenesis.…”
Section: Heterogeneity Within the Masc Populationmentioning
confidence: 99%
“…The presence of pluripotent cells in the adult gland (Hassiotou et al 2012;Roy et al 2013) or the possible persistence of fetal MaSCs into adulthood has profound implications for breast oncogenesis. It is relevant that an embryonic stem cell-like expression profile may be associated with poorly differentiated, aggressive breast tumors (Ben-Porath et al 2008).…”
Section: Heterogeneity Within the Masc Populationmentioning
confidence: 99%
“…Whether these stem/progenitor cell markers identify the same cell populations remains unknown. Furthermore, Tlsty and colleagues discovered that human breast cells can exhibit extensive lineage plasticity (7), which may explain why marker profiles have been difficult to associate with distinct tumor subtypes.…”
Section: Introductionmentioning
confidence: 99%